2015 16th Latin-American Test Symposium (LATS) 2015
DOI: 10.1109/latw.2015.7102516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increasing the fin height on soft error rate and static noise margin in a FinFET-based SRAM cell

Abstract: In this work we investigate the impact of the in height of FinFET transistors on the Soft Error Rate and Static Noise Margin of a FinFET-based SRAM cell. 3-D TCAD environment is used for the analysis. Results show that increases the fin height of FinFET transistors degrades the radiation robustness of the SRAM cell. However, increases the fin height of FinFET transistors improves the Static Noise Margin of the SRAM cell. This suggests that the optimum fin height value of FinFET transistor depends on the SRAM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…6T-SRAM performance factors are shown in Table II. [30][31][32][33] In static operations, R P causes an observable effect under both read and write conditions. On the other hand, for dynamic evaluations, dummy gates cause a minimal increase in parasitic capacitance.…”
Section: Discussion On Parasitic Effects In 6t-srammentioning
confidence: 99%
“…6T-SRAM performance factors are shown in Table II. [30][31][32][33] In static operations, R P causes an observable effect under both read and write conditions. On the other hand, for dynamic evaluations, dummy gates cause a minimal increase in parasitic capacitance.…”
Section: Discussion On Parasitic Effects In 6t-srammentioning
confidence: 99%
“…The use of a Weibull distribution to calculate the soft error rate from the critical charge is only an approximation, but it has nevertheless shown good results for the 65nm node, when compared to silicon measurements [16] and it has been also applied to FinFET technology [11], [17]. Following the SER estimation methodology used in [11], the charge collection efficiency can be computed from the linear energy transfer (LET) value, estimated to 50 fC/μm at ground level for neutrons impacting silicon.…”
Section: Simulation Of Radiation Effectsmentioning
confidence: 99%
“…In recent studies, the soft-error performance of a 6T SRAM cell has been analyzed with sub-nanometer devices. It was found that the FinFET-based SRAM cell showed better immunity due to soft error in comparison with its conventional counterpart, the CMOS SRAM cell [11][12][13]. Moreover, in the literature, a technique called radiation hardening by design (RHBD) is used to eliminate the effect of SEU during circuit level implementation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%